Tri Pusat Pendidikan Sebagai Lembaga Pengembangan Wawasan Keilmuan - Achruh P., H. Andi (Inspiratif Pendidikan, 2016)
Educational institution is viewed as very significant in developing scientific insights and strengthening someone’s creed paradigm as well as instilling steadfastness in worshipping, forming a noble character, and being tolerant towards all of the citizens, so that its presence, wherever it is, is always trying to show the face of Islam as rahmatan li al ‘ālamīn for Indonesian as well a mankind life. This view puts the educational institution as a subsystem of education which is expected to produce human beings who are always trying to improve their faith, piety, and morality, and actively build a civilization and harmony of life, especially in advancing the civilization of a dignified nation. Cautious humans do not only have adequate intelligence but also are supported by a graceful attitude and ability in facing steady current development. There human beings are expected to face tough challenges, obstacles, and changes that occurred in the association community both in the local, regional, national, and global scope.